Through My Eyes - Cole, Cheryl (London Bantam Press, 2010)
An official book from Cheryl Cole that features a series of photos and informal shots from her own personal collection, and gives a glimpse into the life of the nation's favourite star. It explores the other elements of her stratospherically successful career as she takes us behind the scenes at "The X Factor," into the world of L'Oreal.
Include Illustration and Endnote.
Keywords: Singers -- Women singers -- Great Britain